Acoustic Properties of Recycled Polyurethane Foam Waste and Polyvinyl Acetate Composites - Tubelis Jonas; Astrauskas Tomas; Dzikēvičs Miķelis (Environmental and Climate Technologies)
According to a European Commission report, around 675 000 tons of polyurethane foam waste is generated in Europe annually. Only 11 % of this waste is recycled, and the rest goes to landfills or is incinerated, so it is worth looking for new ways to treat or recycle it. This article examines the possibilities of recycling such waste into sound-absorbing materials. With this paper, an alternative way to recycle polyurethane foam is proposed. The purpose of this study is to evaluate the acoustic properties of various polyurethane foam waste scraps in the production of mattresses, pillows, and other products and to assess whether such waste can be used as a basis for creating a sound-absorbing composite material. Research was performed using standard transfer function (ISO 10534-2) and transfer matrix (ASTM E2611) methods. Samples were formed in 3 different thicknesses: 1 cm, 3 cm and 5 cm. Polyurethane (PU) foam waste was used as the main material of the composite. The samples were bound using polyvinyl acetate. Measured parameters: normal incidence sound transmission loss and sound absorption. Sound absorption coefficient (SAC) values of different thickness composite samples reached up to 0.9 in frequencies higher than 1000 Hz (depending on thickness). Sound transmission loss (STL) values increase with thickness and reach 20 dB (5 cm thickness sample). Sound absorption results show that binding material quantity in the composite does not affect sound absorption and sound transmission loss negatively. The aim of this paper is to understand the binding material influence on acoustic properties of PU foam – polyvinyl acetate (PVA) composites.